Синтез элементов энергосистемы по критерию надежности в условиях кибербезопасности - Гриб, Олег Герасимович; Швец, Сергей Викторович; Бортников, А. В. (НТУ "ХПИ", 2017)
Среди аппаратных решений киберзащиты современных энергосистем предложено в их инфраструктуре управления вводить резервирование ключевых элементов для повышения надежности и, тем самым, обеспечения необходимого уровня кибербезопасности. Получены соотношения кратности резервирования элементов для случаев наличия и отсутствия ограничений на минимально допустимые значения вероятностей их безотказной работы.

Among the hardware solutions for cybersecurity of modern power systems, it is proposed in their management infrastructure to introduce redundancy of key elements to increase reliability and thereby ensure the necessary level of cybersecurity. We have obtained the ratio of the multiplicity of the reservation of elements for the cases of presence and absence of restrictions on the minimum permissible values of the probabilities of their trouble-free operation.
Synthesis of power system elements by the criterion of reliability in conditions of cybersecurity
Keywords: резервирование; инфраструктура управления; киберзащита; электроэнергетическая система; ЭЭС; redundancy; management infrastructure